Study of ambient environment around Asymptotic Giant Branch Carbon Star: IRAS 01142+6306 - Khanal, L; Upadhyay, D R; Jha, A K; Aryal, B (BIBECHANA, 2018)
We studied dust environment such as flux, temperature, mass and inclination angle of the cavity structure around the C-rich Asymptotic giant branch star in 60 μm and 100 μm wavelengths band using Infrared Astronomical Survey. We observed the data of AGB star having IRAS name 01142+6306 corresponding to R.A.(J2000)= 01h 17m 33.504s and Dec.(J2000)= 630 22’ 4.98’. Flexible image transport system image was downloaded from Sky View Observatory; we obtained the surrounding flux density using software Aladinv2.5. The dust color average temperature and mass are found to be 25.08 K and 4.731026 kg (0.00024 Mʘ) respectively. The dust color temperature ranges from 18.76 ± 3.16 K to 33.21 ± 4.07 K. The isolated cavity like structure around AGB star has extension 45.67 parsec and contraction 17.02 parsec was observed using detailed calculation. The core region is found to be edge-on having inclination angle 79.46o. BIBECHANA 16 (2019) 31-40